2014
DOI: 10.1038/nrn3707
|View full text |Cite
|
Sign up to set email alerts
|

Growth and folding of the mammalian cerebral cortex: from molecules to malformations

Abstract: The size and extent of folding of the mammalian cerebral cortex are important factors that influence a species’ cognitive abilities and sensorimotor skills. Studies in various animal models and in humans have provided insight into the mechanisms that regulate cortical growth and folding. Both protein-coding genes and microRNAs control cortical size, and recent progress in characterizing basal progenitor cells and the genes that regulate their proliferation has contributed to our understanding of cortical foldi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
416
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 437 publications
(428 citation statements)
references
References 207 publications
(265 reference statements)
9
416
0
3
Order By: Relevance
“…This overlap is consistent with coexpression of Lhx2 in Tbr2-positive (Eomes, T-box brain protein 2) basal progenitors at E15 (Fig. S4B), which generate these neurons (13). Conversely at P7, Lhx2 shows no overlapping staining with Ctip2-positive layer 5 neurons (chicken ovalbumin upstream promoter transcription factor-interacting protein 2) (Fig.…”
Section: Significancesupporting
confidence: 63%
See 1 more Smart Citation
“…This overlap is consistent with coexpression of Lhx2 in Tbr2-positive (Eomes, T-box brain protein 2) basal progenitors at E15 (Fig. S4B), which generate these neurons (13). Conversely at P7, Lhx2 shows no overlapping staining with Ctip2-positive layer 5 neurons (chicken ovalbumin upstream promoter transcription factor-interacting protein 2) (Fig.…”
Section: Significancesupporting
confidence: 63%
“…3B) indicating that cortical progenitors have normal area identities in cKO embryos. Normal expression of TFs that are critical for cortical neurogenesis, such as Pax6 and Tbr2 (13,22), also indicates that the molecular specification and generation of the different cortical layer neurons does not require postmitotic activity of Lhx2. In fact, we analyzed this issue at P7 by using ISH for the specific cortical layer markers Cux2 (Cut-like homeobox 2, layer 2-3), RORb (layer 4), ER81 (layer 5), and Tbr1 (layer 6) and found that cortical layers appear indistinguishable among genotypes (Fig.…”
Section: Significancementioning
confidence: 99%
“…This can be viewed as a forward or direct problem and is very straightforward to perform. Assuming a cortical thickness of 1.2 mm, 29 the result for the stack of Fig. 4 was 88.7 mL∕100 g tissue∕ min which is good agreement with values reported in the literature.…”
Section: Calculation Of Regional Blood Flowsupporting
confidence: 80%
“…These data show BA17 has a thinner cortex compared to more anterior areas. This observation is most likely explained by natural rostro-caudal differences in cortical thickness, rather than ageing-induced neuron loss [28]. Discussion In this study, we have measured Aβ, phosphorylated tau (NFT), microglia, and astrocyte levels in five brain regions and have demonstrated both regional and individual variability in nine non-demented LBC1936 participants.…”
Section: Resultsmentioning
confidence: 98%